Analisis Perubahan Garis Pantai dan Resiliensi Ekologis Pesisir Kabupaten Tangerang Provinsi Banten: Analysis of Coastline Changes and Ecological Resilience in Tangerang Coastal Area, Banten Province (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2023)
The coastal area of ​​Tangerang Regency experiences continuous changes caused by natural factors and human activities. These ongoing changes can affect the level of resilience on the coast. This study aimed to assess the level of resilience based on the dynamics of coastline change and ecological conditions, as well as its relation to land use and land cover on the coast of Tangerang Regency. Data analysis consisted of processing Landsat satellite imagery, land use and land cover (LULC) analysis, and coastline change rate using Digital Shoreline Analysis System (DSAS), oceanographic data processing, and resilience assessment. The results showed that the coast of Tangerang Regency has a low level of resilience, with the dynamics of coastline change being more dominant in erosion than accretion. The rate of coastline change was positively correlated with LULC. Erosion occurred in areas where ponds were dominant, and few mangroves were present, while accretion occurred in estuaries and industrial areas.